2005
DOI: 10.1111/j.1600-0404.2005.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-6: an early marker for outcome in acute ischemic stroke

Abstract: IL-6 seems to be a robust early marker for outcome in acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
127
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(143 citation statements)
references
References 17 publications
11
127
0
5
Order By: Relevance
“…IL-6 in cerebral ischemia S Suzuki et al Tarkowski et al, 1995;Ferrarese et al, 1999;Vila et al, 2000;Acalovschi et al, 2003;Smith et al, 2004;Waje-Andreassen et al, 2005). All of the authors showed that the serum IL-6 level was significantly increased in stroke patients as compared with normal controls.…”
Section: Serum Interleukin-6 In Stroke Patientsmentioning
confidence: 99%
“…IL-6 in cerebral ischemia S Suzuki et al Tarkowski et al, 1995;Ferrarese et al, 1999;Vila et al, 2000;Acalovschi et al, 2003;Smith et al, 2004;Waje-Andreassen et al, 2005). All of the authors showed that the serum IL-6 level was significantly increased in stroke patients as compared with normal controls.…”
Section: Serum Interleukin-6 In Stroke Patientsmentioning
confidence: 99%
“…Stroke elicits a systemic acute phase response and is associated with increased levels of circulating cytokines, acute phase reactants, and elevated neutrophil and total leukocyte counts, which correlate with poor clinical outcome (Muir et al, 1999;Emsley et al, 2003;Smith et al, 2004;Waje-Andreassen et al, 2005;Rallidis et al, 2006). A recent study further highlighted the marked activation of systemic immune pathways after experimental stroke, including induction of cytokines and chemokines in peripheral lymphoid organs (Offner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, structural damage and an aggravated inflammatory response has been correlated with elevated IL-6 levels after brain injury (Howell et al, 2006;Yan et al, 2012). After stroke, for example, elevated levels of IL-6 are associated with the infarct size and poor outcome (Vila et al, 2000;Smith et al, 2004;Waje-Andreassen et al, 2005). In this regard, IL-6 levels are considered a highly specific biomarker of TBI severity and long-term outcome (van Griensven et al, 2003;Howell et al, 2006).…”
mentioning
confidence: 99%